Resolution of the Jiwasraya insurance case: Government perspective on ensuring legal certainty and justice - Saputra, Ferdy; Yusrizal; Bahreisy, Budi; Rasyid, Laila Muhammad (Universitas Ahmad Dahlan, 2025)
Introduction to the Problem: The Jiwasraya insurance scandal exposed major weaknesses in Indonesia’s legal oversight of state-owned enterprises, particularly in corporate governance, fiduciary responsibility, and regulatory enforcement. Despite multiple government interventions, the lack of accountability and transparency eroded public trust and questioned the integrity of legal policy. Purpose/Objective of Study: This article examines the government’s legal and policy measures in addressing the Jiwasraya crisis, focusing on how these efforts align with the principles of legal certainty, justice, and Good Corporate Governance (GCG). Design/Methodology/Approach: Employing a normative juridical method with statute and comparative approaches, the study analyzes statutory frameworks, court decisions, and administrative responses, supported by comparative insights from China, Germany, and the United Kingdom. Findings: The findings reveal that government measures, such as corporate restructuring, the establishment of IFG Life, and criminal prosecution, remain largely reactive and lack structural reform. The study argues for the codification of fiduciary duties, strengthening corporate criminal liability, and the selective imposition of severe penalties in corruption cases causing extensive state losses. Furthermore, the absence of transitional legal norms and enforceable state guarantees leaves non-migrated policyholders without legal protection. These findings highlight the urgency of reforming Indonesia’s corporate and financial governance system to restore legal certainty and uphold justice. Paper Type: Research Article